Science and religion in a post-colonial world : interfaith perspectives - Bagir, Zainal Abidin (Adelaide : ATF Press, 2005)
This book addresses selected issues in the emerging field of science and religion, and at the same time acknowledges the situation of Indonesia (or, more generally, a "Third World" country) as the locus for this discussion. The book is concerned with how various world religions, in particular Islam and Christianity respond to shared challenges posed by science, as new theories in cosmology, physics, and the life sciences have brought challenges to many traditional religious ideas. There are also more generally epistemological challenges that reflect the recent success of natural science as a mode of inquiry. These are felt as problems in both the Western and non-Western worlds, but with an important difference. While the Western world is considered the "legitimate owner" of modern science, some in the Muslim world, and the Third World more generally, see modern science as a cultural alien imposed on them, due to its initial introduction in the colonial period.
Humanity as an endangered species in science and religion / Steve Fuller --Vedic science and Hindu nationalism : arguments against a premature synthesis of religion and science / Meera Nanda--Islam, science and "Islamic science" : how to "integrate" science and religion / Zainal Abidin Bagir --Perceiving God in the lawfulness of nature : scientific and religious reflections / Philip Clayton--Sacred science vs. secular science / Mehdi Golshani --Science and idea of the sacred / Osman Bakar --Cosmology and the quest for meaning / Karlina Leksono-Supelli --How did the universe begin? : cosmology and a metaphysics for the twenty-first century / Bruno Guiderdoni --Big bang cosmology and creation theology : towards a fruitful dialogue between science and religion / Justin Sudarminta --Towards a constructive theology of evolution / William Grassie --Creation or evolution? : the reception of Darwinism in modern Arab thought / Mahmoud M Ayoub --Creation and evolution : Islamic perspectives / Teuku Jacob --The care of the earth : religion, science, and sustainable community / Larry Rasmussen.
"All chapters in this book come from a conference organized by the Center for Religious and Cross-Cultural Studies of Gadjah Mada University, Yogyakarta, Indonesia
Keywords: Religion and science -- Congresses